Manajemen Risiko Bencana Gempa Bumi Berbasis Analytical Hierarchy Process Di Wilayah Rawan Gempa Bumi: Studi Kasus Provinsi Banten - Gunawan, Rahmad; Brantas Suharyo G; Imer HPS; Ima Damayanti; Hotma RS; Purnomo Yusgiantoro; I Wayan Medio (Jurnal Geografi, Edukasi dan Lingkungan (JGEL), 2025)
Earthquake disasters are feared by many people, especially people who live in disaster-prone areas such as coasts, mountains and other vulnerable areas. The physical threat posed by earthquake disasters, the psychological and economic impacts arising from loss of life, destruction of property, and social disruption are also enormous. Disaster risk management is important because it is expected to minimize threats, reduce vulnerability and increase the capacity of threatened areas. This research is to find the best alternative in strategic decision making that can be used in implementing earthquake disaster risk management with variable factors of danger, vulnerability and increasing community resilience. This research uses a qualitative method which processes the data through the Analytical Hierarchy Process (AHP) with a case study of earthquake-prone areas in Banten Province. The research sites were carried out in Serang Regency, Cilegon Regency, Pandeglang Regency and Lebak Regency, Banten Province, which are earthquake-prone areas. Improving earthquake disaster management infrastructure is a top priority in reducing risks due to earthquake disasters because it can minimize threats, reduce vulnerability and increase the capacity of threatened areas, especially in the Banten Province area by improving the quality of public facilities, evacuation facilities and infrastructure as well as regulations regarding improving the quality of buildings. residences and industries that are standardized to be earthquake resistant.